Fenomena Career Plateau Tenaga Pemasar Bank BUMN Dengan Moderasi Kepemimpinan Pemberdayaan (Empowering Leadership). (Studi Kasus PT. Bank Rakyat Indonesia (Persero), Tbk Regional Office Surabaya) - Poltak Dedy Warta Kesuma Gultom; Teofilus Teofilus (Jurnal Impresi Indonesia, 2025)
The workforce in a company has a career cycle that must be managed well, especially in the position of marketing staff. Marketing staff are involved in the internal dimensions of the organization as well as unique external elements every day. The function of marketing staff in a production or service company is very vital, considering that the success of a company selling products or services is highly dependent on the success of the marketing sector so that every phase that affects the productivity of marketers must be an important concern for the organization. Career Plateau is a phase in a professional career where the possibility of job promotion is getting smaller and the type and quality of work become monotonous. A situation where marketers feel trapped with no way to advance or move up in the company even though each individual has tried to improve their performance and develop their skills experiences structural career stagnation which can result in discomfort, discomfort can cause cynicism and cynicism can trigger inertia. In this study, Empowering leadership has a significant moderation of the relationship between discomfort and cynicism so that employees are more motivated to work, feel appreciated and participate in achieving organizational goals, however, Empowering leadership does not have a significant role in moderating the relationship between cynicism and inertia. Inertia cannot be reduced by empowerment patterns. Radical changes are needed to the corporate culture through cultural transformation, policy overhaul and renewal of the human capital system.